(untitled) (Eureka Journal of Health Sciences & Medical Innovation, 2026)
Latent tuberculosis infection (LTBI) remains a significant global public health concern. Approximately one-quarter of the world’s population is estimated to be infected with Mycobacterium tuberculosis, with most individuals harboring the bacteria in a latent state. Although these individuals do not exhibit symptoms and are not contagious, they remain at risk of developing active tuberculosis (TB) disease during their lifetime. Early diagnosis of LTBI is essential for preventing disease progression and reducing TB transmission. This article reviews the epidemiology, risk factors, diagnostic methods, advantages and limitations of available tests, and current recommendations for diagnosing latent tuberculosis infection in adults.